Women’s empowerment in agriculture and nutritional outcomes: Evidence from six countries in Africa and Asia - Quisumbing, Agnes R.; Sproule, Kathryn; Martinez, Elena M.; Malapit, Hazel J. (International Food Policy Research Institute, 2020)
Although women’s empowerment and gender equality are associated with better maternal and child nutrition outcomes, recent systematic reviews find inconclusive evidence. This paper applies a comparable methodology to data on the Women’s Empowerment in Agriculture Index (WEAI), a recent internationally-validated measure based on interviews of women and men within the same household, from six countries in Africa and Asia to identify which dimensions of women’s empowerment are related to household-, women-, and child-level dietary and nutrition outcomes. We examine the relationship between women’s empowerment and household-level food security and dietary diversity; women’s dietary diversity and BMI; and child-related outcomes, controlling for woman, child, and household characteristics. We also test whether women’s empowerment has differential associations for boys and girls. We do not find consistent associations between dimensions of empowerment and food security and nutrition outcomes across countries, but some patterns emerge. Overall empowerment scores are more strongly associated with nutritional outcomes in the South Asian countries in our sample compared to the African ones. Where significant, greater intrahousehold gender equality is associated with better nutritional outcomes. However, different domains have different associations with nutritional outcomes, suggesting that tradeoffs exist: higher workloads are associated with more diverse diets but lower women’s BMI and child anthropometric outcomes. Identifying the overlap between the top contributors to disempowerment and those most strongly related to nutrition outcomes can inform the design and implementation of nutrition-sensitive agricultural programs.